Mikrohistorie, mikrometraże i mikrodokumenty. O skomplikowanych relacjach historii i form lapidarnych w audiowizualnej kulturze cyfrowej - Sołodki, Paweł (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
This article uses the categories of microhistory, microshort and microdocumentary, for which the context is contemporary digital environments, with a particular emphasis on social media. As microhistory as a research method and microshort and microdocumentary as concise audiovisual forms are underrepresented categories in contemporary historiography and film studies, the author juxtaposes them in the text, examining the points of intersection between them and the resulting phenomena. The aim of the article is to answer the following questions: (1) To what extent is it possible to analyse microdocumentaries using micro-historical tools?; (2) To what extent is it possible to integrate microdocumentaries into the scope of micro-historical research?; (3) How can this juxtaposition broaden the realisation and research scope of both microshorts and microhistory?